Solar drying of pine lumber: Verification of a mathematical model - Bekkioui, Naoual; Hakam, Abdelillah; Zoulalian, André; Sesbou, Abdessadek; El Kortbi, Mohamed (Maderas. Ciencia y Tecnología, 2025)
This work presents verification of a mathematical model for drying of a wood stack in a greenhouse type solar dryer. A simplified heat and mass transfer numerical model has been developed with input parameters based on the actual metrological data of a Moroccan climate. For its validation, a comparative study is performed in this work; the present model is solved to simulate the solar drying of pine wood using experimental data of previous wood drying experiments. The average relative discrepancies between the model predicted and experimental data are 1,2% for wood moisture content, 1% for drying air temperature and 5% for the air relative humidity. The close agreement between the predicted and experimental results shows the ability of the model to reproduce experimental drying data for wood.